2010
DOI: 10.1080/13607861003587610
|View full text |Cite
|
Sign up to set email alerts
|

Lying in dementia care: An example of a culture that deceives in people's best interests

Abstract: This study contributes to a more informed understanding regarding both the definition and use of lies. On the whole, participants developed a less generic perspective about lying, becoming more supportive of lies when used in specific situations in the best interests of the recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 11 publications
2
52
0
3
Order By: Relevance
“…While researchers have highlighted the issue of duplicity in caregiving and the kinds of ethical dilemmas it can create (see Blum, 1994; Elvish, James & Milne, 2010; Strech, Mertz, Knüppel, Neitzke, & Schmidhuber, 2013), the current study identifies the turning point in the social process of care when family members began using duplicitous techniques. The evidence shows that they began using these techniques (identified herein as restrictive unilateral autonomy management techniques) as a self-conscious strategy when the elder’s awareness ability was thought to have declined severely enough to make transparent negotiation difficult.…”
Section: Discussionmentioning
confidence: 93%
“…While researchers have highlighted the issue of duplicity in caregiving and the kinds of ethical dilemmas it can create (see Blum, 1994; Elvish, James & Milne, 2010; Strech, Mertz, Knüppel, Neitzke, & Schmidhuber, 2013), the current study identifies the turning point in the social process of care when family members began using duplicitous techniques. The evidence shows that they began using these techniques (identified herein as restrictive unilateral autonomy management techniques) as a self-conscious strategy when the elder’s awareness ability was thought to have declined severely enough to make transparent negotiation difficult.…”
Section: Discussionmentioning
confidence: 93%
“…Some authors contend that lying is morally distinct from deception (Benn, 2001;Jackson, 2001), whereas others argue that both acts in clinical practice are ethically akin, because they are both a deliberate abuse of power and an "affront" to patient dignity (Bakhurst, 1992). Whatever the terminology used, empirical studies demonstrate that decision-making about honest communication is a common issue faced by professionals caring for patients with dementia (Day, James, Meyer & Lee, 2011;Elvish, James & Milne, 2010;James, Wood-Mitchell, Waterworth, Mackenzie & Cunningham, 2006;Tuckett, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…As regards our immediate interests, for example, current evidence suggests that lying and deception are common practice in the care of people with dementia, albeit often well intended to prevent distress to the person with dementia. For example, Elvish, James, and Milne () found that 97% of people in paid care for people with dementia lied for various reasons. These included protecting the person from distress, for example to avoid retelling them of the death of a loved one, or to encourage them to do something that would avoid potential harm at a later stage, such as keeping a chiropodist appointment.…”
Section: Selfhood Truth and Deception In The Context Of Dementiamentioning
confidence: 99%